Documentation of Symptoms in Children Newly Diagnosed With Cancer Highlights the Need for Routine Assessment Using Self-report. Issue 6 (November 2021) - Bradford, Natalie K.; Bowers, Alison; Chan, Raymond Javan; Walker, Rick; Herbert, Anthony; Cashion, Christine; Condon, Paula; Yates, Patsy
Abstract : Background: Symptom management is a cornerstone of quality care and has the potential to vastly influence patient experiences. The supportive care needs of children, however, are not well described. Objective: The aims of this study were to describe documentation about assessment and occurrence of symptoms in medical records of children with cancer and to compare the profile of documented symptoms with child self-report. Methods: Twelve weeks of medical records of children (8–18 years) newly diagnosed with cancer were reviewed, and data were extracted regarding symptom assessment and occurrence. A second cohort of children attending oncology outpatients completed the electronic Symptom Screening in Pediatrics self-report of symptom bother. They also answered additional questions about other symptoms and the experience of self-report. We evaluated the profile of symptoms recorded as assessed by healthcare providers and self-reported by children. Results: One thousand three hundred sixteen symptoms were identified in 3642 assessments. The symptoms most commonly documented by medical and nursing staff were nausea, pain, and appetite. Allied health staff most frequently documented fatigue, feeling scared, or sad. Forty-eight children completed self-report for the same symptoms and identified fatigue, appetite, and taste were the most bothersome. Children were positive about the experience of completing self-report. Conclusion: This study adds further to the evidence about the importance of obtaining information beyond routine clinical assessment from children themselves. Implications for Practice: Healthcare providers do not routinely identify all distressing symptoms during clinical encounters. Use of patient-reported outcome measures in children is feasible and acceptable and empowers children to communicate about symptoms, which can facilitate prompt intervention.